Hearing evaluation with ABR in pediatric patients with celiac disease - Yaprak, Neslihan; Sayar, Ersin; Derin, Alper Tunga; Bostancı, Aslı; Turhan, Murat; Yılmaz, Aygen (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Celiac disease (CD) is an autoimmune and genetic disease that is triggered by gluten intolerance. We aimed to investigate whether Celiac disease have any effect on Auditory Brainstem Response (ABR) waves compare to a healthy control group, and present its association with sensorineural hearing loss (SNHL). Materials and Methods: Thirty-eight patients aged 2 to 16 years old were included in the study. The patients had confirmed diagnosis of Celiac disease through duodenal biopsies and transglutaminase Antibody (Ab) (+). The control group consisted of 18 children aged 3 to 17 years old who were all admitted to the pediatric gastroenterology department due to complaints of constipation and transglutaminase Ab (-).All children underwent Auditory-Brain-Stem-Evoked Responses (ABR). The data were gathered using click stimulus at 10/s frequency 90dB HL. Results: The results of ABR examination did not show any difference between the patient group and control group as regards the latency of the waves I, III, V. No difference was observed between the two groups in the interpeak latecies I-III, I-V and III-V. None of the patients was observed to have clinical hearing loss. Discussion: The exact pathogenesis of neurological damages observed in Celiac disease is still unknown. Humoral immune mechanisms are the most frequently attributed cause. Conclusion: Although no significant difference was found in hearing values between the study group and healthy control group, there is a need for further research on this subject.